THE ABILITY OF WATER HYACINTH (Eichhornia crassipes) AS A BIOACCUMULATOR OF HEAVY METALS IN WASTEWATER FROM THE RUBBER PROCESSING INDUSTRY - Rusdi Hasan; Tia Setiawati; Nopriyeni Nopriyeni (JURNAL BIOEDUKASI, 2025)
This study aimed to assess the ability of water hyacinth (Eichhornia crassipes) as a bioaccumulator of heavy metals copper (Cu) and zinc (Zn) in rubber industry wastewater at PT Batanghari, Bengkulu. The research methods included water and water hyacinth sampling from effluent ponds and controls, followed by analysis of Cu and Zn levels using atomic absorption spectrophotometry (AAS). Results showed that Zn levels in wastewater reached 143.0884 mg/l (28 times the quality standard), while Cu was 0.1845 mg/l (still below the quality standard). Water hyacinth accumulated metals in different patterns: Cu was highest in the roots (1.4480 mg/l), while Zn was evenly distributed in the roots (6.7261 mg/l) and leaves (6.6473 mg/l). Analysis of bioaccumulation (BAF) and translocation factors (TF) revealed the efficiency of water hyacinth in absorbing metals, especially Zn, although the absorption mechanism is selective and influenced by environmental conditions such as pH, dissolved oxygen, and the presence of organic compounds. The implications of this study emphasize the potential of water hyacinth as an economical and sustainable phytoremediation solution for the rubber industry, with recommendations of implementing a constructed wetland system and periodic harvesting for optimization.